To Enhance Student’s Writing Ability in English Through the Use of Picsart Pictures for 5th-Grade Students at SDN Gelam 1 Candi Sidoarjo - -, Tri Andayani; Anik Ida Fauziah; Sulistyanimgsih; Ellys Suliyah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
This research was conducted to determine the usefulness and benefits of Picsart images as a teaching strategy to enhance the teaching of writing skills to students. The method employed in this study was the method of classroom action research, which was carried out in two cycles. The subjects or participants in this study were grade 5 students of SDN Gelam 1 Sidoarjo, totaling 26 students. Researchers collected data from students' test results on implementing Picsart images in writing text. Additionally, data was also obtained through observations made during the learning process. Based on the results of the study, Students' writing ability scores using picsArt, in Pre-cycle scored ≥ 70 (42%) , Cycle 1 scored ≥ 70 (65,38%), and Cycle 2 scored ≥ 70 (100%). The scores reflecting students' writing ability, as assessed through picsArt, demonstrated improvement in 15 students, or 58%, when comparing the pre-cycle period to cycle 2. It was proven that the use of Picsart images could improve students' learning abilities. Their ability increased after using Picsart images as a strategy in writing text. This research reflects positive perceptions among students regarding the use of PicsArt images in improving their writing skills, with significant benefits seen in creativity, expression, and overall writing quality.